Petri Nets Modeling of a Flexible Manufacturing System - Ala, Balti; Yahyaoui, Amel; Lakhoua, Mohamed Najah (Journal of Innovation and Applied Technology, 2024)
- In a world where industrial mechatronic systems evolve from day to day, the intensity of these requirements influences the maximization of efficiency, the optimization of the safety of the working environment including human and the increase of the quality of services. This is why industrial computing is becoming a necessity for manufacturers and even researchers working on innovative and creative subjects.This paper deals with the analysis and the modeling of a flexible manufacturing system. Firstly, the study of the system engineeringthen the composition of the studied system was presented. Second, we present an application of a modeling based on Petri Nets.Finally, the last present conclusion and future work.